29 Inverting the wellbeing pyramid: the GOSH approach to looking after staff wellbeing. (30th November 2020) - Bryon, Mandy; Hothi, Daljit; Soon, Kristina
Abstract : At the start of the COVID-19 pandemic experts in trauma and psychology advised about the importance of ensuring the mental and emotional well-being of staff was being considered and supported. Most of the literature and experts advocated a layered, hierarchical intervention approach. At Great Ormond Street Hospital (GOSH) we elected to 'invert the pyramid', mobilising the 'specialists/experts' to create a virtual well-being hub and that overtime layering and blending other interventions as suggested in this classical model. One of the key successes of the COVID crisis at GOSH has been our ability to raise the profile and importance of staff well-being across the organisation and this has been well received. The hub continues to remain the centre of our work and has been active identifying, triaging and providing psychological first aid or referring staff for external mental health treatment. In the recovery phase we have extended the 'expertise' to Peer Support Workers, TRiM Practitioners and Well-being Coaches that have collectively formed a pan-trust well-being network to meet the needs of the COVID-19 but also the smaller, repeated and significant traumas that we face when working in healthcare .